Molybdenum Reduction to Molybdenum Blue in Serratia sp. Strain DRY5 Is Catalyzed by a Novel Molybdenum-Reducing Enzyme. (3rd March 2014) - Shukor, M. Y.; Halmi, M. I. E.; Rahman, M. F. A.; Shamaan, N. A.; Syed, M. A.
Abstract : The first purification of the Mo-reducing enzyme from Serratia sp. strain DRY5 that is responsible for molybdenum reduction to molybdenum blue in the bacterium is reported. The monomeric enzyme has an apparent molecular weight of 105 kDalton. The isoelectric point of this enzyme was 7.55. The enzyme has an optimum pH of 6.0 and maximum activity between 25 and 35°C. The Mo-reducing enzyme was extremely sensitive to temperatures above 50°C (between 54 and 70°C). A plot of initial rates against substrate concentrations at 15 mM 12-MP registered a V m a x for NADH at 12.0 nmole Mo blue/min/mg protein. The apparent K m for NADH was 0.79 mM. At 5 mM NADH, the apparent V m a x and apparent K m values for 12-MP of 12.05 nmole/min/mg protein and 3.87 mM, respectively, were obtained. The catalytic efficiency (k c a t /K m ) of the Mo-reducing enzyme was 5.47 M - 1  s - 1 . The purification of this enzyme could probably help to solve the phenomenon of molybdenum reduction to molybdenum blue first reported in 1896 and would be useful for the understanding of the underlying mechanism in molybdenum bioremediation involving bioreduction.